Emission-intensity-enhanced GaN-based LED based on multilayer grating structures - Li, Xin; Sun, Dejie; Cao, Lijun; Guo, Shiliang; Li, Zhiquang (Oficyna Wydawnicza Politechniki Wrocławskiej, 2021)
A novel surface-plasmon-enhanced GaN-LED is proposed to improve the emission efficiency of the traditional LED. The SiO2 film, Ag triangular structure and ITO film were coated on the rectangularly-patterned p-GaN layer sequentially, which can form the quasi-symmetrical waveguide structure to enhance the internal quantum efficiency and the light extraction efficiency. The COMSOL software is used to simulate the LED structure. The radiated powers, absorbed powers and distribution of electric field are obtained and analyzed. The results reveal that emission efficiency of the proposed GaN-LED can be greatly improved.
Optica Applicata, Vol. 51, 2021, nr 4, s. 529-540
Optica Applicata is an international journal, published in a non-periodical form in the years 1971-1973 and quarterly since 1973. From the beginning of the year 2008, Optica Applicata is an Open Access journal available online via the Internet, with free access to the full text of articles serving the best interests of the scientific community. The journal is abstracted and indexed in: Chemical Abstracts, Compendex, Current Contents, Inspec, Referativnyj Zhurnal, SCI Expanded, Scopus, Ulrich’s Periodicals Directory
http://opticaapplicata.pwr.edu.pl/
Keywords: optyka; light-emitting diode; surface plasmons; grating; quantum wells